Effects of different harvest frequencies on microbial community and metabolomic properties of annual ryegrass silage - Fu, Zhihui; Sun, Lin; Hou, Meiling; Hao, Junfeng; Lu, Qiang; Liu, Tingyu; Ren, Xiuzhen; Jia, Yushan; Wang, ZhiJun; Ge, Gentu (Frontiers in Microbiology, 2022)
In this study, we analyzed the fermentation quality, microbial community and metabolome characteristics of ryegrass silage from different harvests (first harvest-AK, second harvest-BK, third harvest-CK) and analyzed the correlation between fermentative bacteria and metabolites. The bacterial community and metabolomic characteristics were analyzed by single molecule real-time (SMRT) sequencing and ultra high performance liquid chromatography-mass spectrometry (UHPLC-MS/MS), respectively. After 60 days of ensiling, the pH of BK was significantly lower than those of AK and CK, and its lactic acid content was significantly higher than those of AK and CK. Lactiplantibacillus and Enterococcus genera dominate the microbiota of silage obtained from ryegrass harvesting at three different times. In addition, the BK group had the highest abundance of Lactiplantibacillus plantarum (58.66%) and the CK group had the highest abundance of Enterococcus faecalis (42.88%). The most annotated metabolites among the differential metabolites of different harvests were peptides, and 8 amino acids were dominant in the composition of the identified peptides. In the ryegrass silage, arginine biosynthesis, alanine, aspartate and glutamate biosynthesis had the highest enrichment ratio in the metabolic pathway of KEGG pathway enrichment analysis. Valyl-isoleucine and glutamylvaline were positively correlated with Lactiplantibacillus plantarum. D-Pipecolic acid and L-Glutamic acid were positively correlated with Levilactobacillus brevis. L-phenylalanyl-L-proline, 3,4,5-trihydroxy-6-(2-methoxybenzoyloxy)oxane-2-carboxylic acid and shikimic acid were negatively correlated with Levilactobacillus brevis. In conclusion, this study explains the effects of different harvest frequency on the fermentation quality, microbial community and metabolites of ryegrass, and improves our understanding of the ensiling mechanisms associated with different ryegrass harvesting frequency.